Band-like transporting and thermally durable V-shaped organic semiconductors with a phenyl key block. Issue 40 (1st October 2020) - Sawabe, Chizuru; Kumagai, Shohei; Mitani, Masato; Ishii, Hiroyuki; Yamagishi, Masakazu; Sagayama, Hajime; Kumai, Reiji; Sato, Hiroyasu; Takeya, Jun; Okamoto, Toshihiro
Abstract : Sulphur-containing V-shaped π-electron systems with substituents based on a phenyl key block exhibit band-like hole transport and high thermal durability. Abstract : Towards the development of high-performance small molecule-based organic semiconductors with high carrier mobility and high thermal durability, strategic and systematic investigations are needed for not only molecular design of π-electron cores and substituents but also fundamental and structural analyses. Here, we focus on the sulphur-containing V-shaped π-electron systems with phenyl substituents and carry out comprehensive analyses of molecular assembly and charge-transport properties. Phenyl- and decyl-phenyl-substituted DNT-V s (Ph-DNT-VW and C10 Ph-DNT-VW ) are readily synthesized through a versatile synthetic procedure. Single crystal data and their theoretical calculations suggested that both compounds form typical herringbone-type packing structures that are favorable for two-dimensional charge-transporting capability. Indeed, single-crystal transistors of Ph-DNT-VW and C10 Ph-DNT-VW have excellent mobility of 3.1 and 8.1 cm 2 V −1 s −1 . Furthermore, their negative temperature coefficients of mobility strongly suggest band-like transport characteristics. Finally, solution-processed thin-film transistors of C10 Ph-DNT-VW exhibit high thermal durability up to 180 °C, which is an essential feature for practical electronics.